1997
DOI: 10.1046/j.1365-2249.1997.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell-mediated fatal hyperinflammatory reactions in mice infected with Penicillium marneffei

Abstract: SUMMARYIn the present study, we demonstrate that all mice survived when a low dose of Penicillium marneffei was instilled intratracheally, while severe infection induced by instillation of 1 × 10 8 and 1 × 10 7 colony-forming units (CFU) killed all and 50% of mice, respectively, within 14 days, although the number of live microorganisms in the lungs of these animals was found to decrease with time. The cellular inflammatory responses in the lungs were much more striking in mice with severe infection than in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A clinical strain of P. marneffei, designated H1140 [36], was recently registered by American Type Culture Collection (ATCC 201013). The method of preparation of conidial suspensions was described in our previous study [36].…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical strain of P. marneffei, designated H1140 [36], was recently registered by American Type Culture Collection (ATCC 201013). The method of preparation of conidial suspensions was described in our previous study [36].…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…A clinical strain of P. marneffei, designated H1140 [36], was recently registered by American Type Culture Collection (ATCC 201013). The method of preparation of conidial suspensions was described in our previous study [36]. For preparing inocula of yeast cells, conidia were incubated in brain heart infusion broth (BHI; Eiken) at 37ЊC for 7-14 days, as described in a previous study [37].…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…Untreated disseminated disease is often fatal. Experiments in mice have shown that, in the absence of immunosuppression, infections with high numbers of conidia (4 Â 10 5 ) are eventually cleared, whereas athymic mice die from the infection (Kudeken et al 1997). This shows that immune status of the host is a key factor in the outcome of infection.…”
Section: Talaromyces Marneffeimentioning
confidence: 99%